Anomalous enrichment of molybdenum and associated metals in Lower Jurassic (Lias Group) black shales of central England, as revealed by systematic geochemical surveys. Issue 3 (June 2015) - Breward, N.; Kemp, S.J.; Ambrose, K.; Powell, J.H.; Morigi, A.; Wagner, D.
Abstract Systematic multi-media geochemical surveying by the British Geological Survey's Geochemical Baseline Survey of the Environment (G-BASE) project has revealed significant anomalous patterns of enrichment for a suite of elements – copper (Cu) and uranium (U) – with exceptionally high levels of molybdenum (Mo), in soils and stream sediments in central England. Enrichment of these elements is most often associated with organic-rich, sulphidic 'black shale' lithofacies, typical of oxygen-deficient, euxinic depositional environments. The main anomaly lies between Evesham and Rugby where the bedrock comprises the Blue Lias and Charmouth Mudstone formations. Concentrations of Mo are particularly high, reaching soil values of 50 mg/kg, where the regional background is <2 mg/kg. Analysis of black shale partings sampled from rhythmic limestone–shale couplets reveal Mo levels up to 320 mg/kg. Complementary X-ray diffraction analyses suggest that the anomalous Mo levels are hosted by sulphidic (pyrite) rather than organic phases. High Mo levels may have significant impacts on local agriculture, as well as revealing hitherto unsuspected periods of hypoxic and anoxic bottom water sedimentation within localised basins in central England during the Early Jurassic. Rhythmic alternations of thin beds of Mo-rich, sulphidic black shale (euxinic) with bioclastic and micritic limestone (oxic) represent primary depositional cycles rather than a diagenetic origin. The bed-scale cyclicity is attributed to previously described orbitally-induced precession cycles that influenced climate. These resulted in periods of basin anoxia and black shale sedimentation during periods of enhanced terrestrial fresh-water run-off (possibly below a low-salinity pycnocline), alternating with periods of oxygenation of the sea-water and bottom sediments during overturn of the water column.